2019
DOI: 10.3390/pharmaceutics11120688
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Resveratrol Nanosuspension Using the Antisolvent Precipitation Method without Solvent Removal, Based on a Quality by Design (QbD) Approach

Abstract: The purpose of this study was to develop a resveratrol nanosuspension with enhanced oral bioavailability, based on an understanding of the formulation and process parameters of nanosuspensions and using a quality by design (QbD) approach. Particularly, the antisolvent method, which requires no solvent removal and no heating, is newly applied to prepare resveratrol nanosuspension. To ensure the quality of the resveratrol nanosuspensions, a quality target product profile (QTPP) was defined. The particle size (z-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…However, it should be noted that the low bioavailability and rapid metabolism of resveratrol in the body not only limits its therapeutic and biological effects, but also causes some changes in the way resveratrol is administered. In fact, numerous studies have been conducted to improve the bioavailability of resveratrol, and an important method of administering resveratrol is nano-based systems [ 87 ]. Interestingly, it has been reported that lipid nano-capsules loaded with resveratrol have higher anti-oxidant and anti-inflammatory effects than resveratrol alone [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the low bioavailability and rapid metabolism of resveratrol in the body not only limits its therapeutic and biological effects, but also causes some changes in the way resveratrol is administered. In fact, numerous studies have been conducted to improve the bioavailability of resveratrol, and an important method of administering resveratrol is nano-based systems [ 87 ]. Interestingly, it has been reported that lipid nano-capsules loaded with resveratrol have higher anti-oxidant and anti-inflammatory effects than resveratrol alone [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were centrifuged (12,000 rpm, 5 min), and plasma was collected and stored at −70 • C until HPLC analysis. The concentration of trans-resveratrol in plasma was determined using a previously reported method and under HPLC analysis conditions [16,41]. The AUC 0→8h was calculated using the linear trapezoidal method.…”
Section: Pharmacokinetic Study In Ratsmentioning
confidence: 99%
“…Further, its benefits are affected after its oral administration owing to its poor solubility and instability in physiological conditions as well as extensive metabolism [8,9]. To date, several formulation strategies such as amorphous solid dispersions, composite nanoparticles, emulsions, liposomes, polymeric micelles, self-emulsifying drug delivery systems, and solid lipid nanoparticles have been investigated to resolve this problem [10][11][12][13][14][15][16][17][18][19]. In addition, the enhanced oral bioavailability in humans has been reported with lipid formulation, micellar liquid formulation, and microparticles mixed with a liquid formulation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is obvious that poor bioavailability of resveratrol not only has limited its therapeutic and biological impacts, but also has led to some effects on the administration route of resveratrol. A variety of attempts have been performed to improve the bioavailability of resveratrol and among them, the nano-based drug delivery systems are of importance [35]. In a newly published article, Thipe and colleagues synthesized resveratrol-loaded gold nanoparticles to enhance the anti-tumor potential of resveratrol against breast, pancreatic and prostate cancers.…”
Section: Resveratrolmentioning
confidence: 99%